Dunlap and the Exoduster Connection - Jan Houston (Symphony in the Flint Hills, 2012)
Following the Civil War, Federal troops remained in the South, maintaining order and overseeing the Reconstruction period. Black freedmen trusted that they would gain the rights of free men everywhere: the right to vote, the right to education, the right
Keywords: Civil War; blacks; freedom; African American; slave; slavery; South; North; Union; Confederate; vote; rights; human right; land; education; freedmen; farming; Redemption; Pap Singleton; Dunlap; Kaw Indians; Native Americans; people; stock; ranch; Great Ex